Association between histo-blood group antigens and Pseudomonas aeruginosa-associated diarrheal diseases - Chih-Hsien Chuang; Rajendra Prasad Janapatla; Yi-Hsin Wang; Hsin-Ju Chang; Chyi-Liang Chen; Cheng-Hsun Chiu (Journal of Microbiology, Immunology and Infection, 2023)
Background: Pseudomonas aeruginosa is not a common enteric pathogen. The association between human histo-blood group antigens (HBGAs) and P. aeruginosa enteric infection has not yet been studied. Methods: We collected stool samples from healthy children under 2 years of age for P. aeruginosa gut colonization rate. Saliva samples were collected from patients with P. aeruginosa-associated diarrheal diseases and normal healthy children. Genomic DNA was extracted from saliva samples for ABO blood group typing and FUT2 genotyping. Lewis phenotype was detected using ELISA assay. Results: A total of 85 patients with P. aeruginosa-associated diarrheal diseases and 105 healthy children were enrolled for collecting saliva specimens. The stool colonization rate was 5/101 (5%) in healthy children, 4/58 (6.9%) in infants, and 1/43 (2.3%) in children 1–2 years old, respectively. Blood group A was more frequent in patients with P. aeruginosa-associated diarrheal diseases 24/77 (31.2%) than in healthy children 18/102 (17.6%) (P = 0.035). All patients and healthy children were secretor positive. The distribution of weak-secretor genotype Se385/Se385 was 23/84 (27.4%) in patients with P. aeruginosa-associated diarrheal diseases and 17/104 (16.3%) in healthy children, respectively (P = 0.06). Patients with P. aeruginosa-associated diarrheal diseases had a higher percentage of Lea+b+ phenotype 25/81 (30.9%) than healthy children 17/105 (16.2%) (P = 0.018). There was no association between ABO or secretor or Lewis status with the clinical severity of P. aeruginosa-associated diarrheal diseases. Conclusion: Infants had a higher gut P. aeruginosa colonization rate than children. Children with blood group A and Lea+b+ phenotype are prone to P. aeruginosa-associated diarrheal diseases.